Assessment of water, sanitation, and hygiene among women living in precarious households in a Turkish urban area - Sera Şimşek; Zeliha Aslı Öcek; Meral Türk; Ayşegül Ünver (BMC, 2024)
Abstract Background This study aimed to identify the determinants of water, sanitation, and hygiene (WASH) behaviors and conditions among women in poor neighborhoods in Izmir, Turkey, and to develop a scale for assessing WASH behaviors and conditions that is specifically designed for use in precarious urban areas. Methods The study used a cross-sectional design, as well as a methodological feature for developing the scale. The sample size was calculated as 243 households out of 2667 households in the Basmane neighborhood, with a 95% confidence interval and a 6% margin of error, and a woman who was responsible for cleaning was invited to participate from each household. The scales for WASH behaviors and conditions, which served as dependent variables, were developed in a four-stage process, yielding two distinct scales. The WASH-Behaviors Scale had 14 items about hand, body, and home hygiene, whereas the WASH-Conditions in Households Scale included 16 items about variables like area per capita, physical structure, and cleaning tool availability. Age, ethnicity, number of children, education, work status, and income were among the independent variables. Data was collected through household visits. The scales' validity was evaluated using exploratory factor analysis. Linear logistic regression analysis was employed to assess the determinants of WASH behaviors. Results The women, with an average age of 40.65 ± 14.35 years, faced economic challenges, as a substantial portion earned an income below the minimum wage. More than half of them were uninsured, and 72.6% were identified as migrants or refugees. Factor analysis confirmed the compatibility of both scales (KMO = 0.78-0.80, p < 0.05), elucidating 52-54% of the total variance. Factors such as ethnicity, number of children, husband's education level, income perception, and WASH conditions explained 48% of WASH behaviors. Conclusions WASH-Behaviors and WASH-Conditions in Households scales met the validity criterion, and their scores were related to basic sociodemographic and economic characteristics like education, income, household size, and ethnicity. The scale development process emphasized the importance of considering both behaviors and household conditions, albeit using different techniques. The findings indicated that WASH conditions are more problematic than behaviors, and that behavioral interventions will not work unless the conditions are corrected.